Comparison of high strength steels with different aluminium and manganese contents using dilatometry - Hajsman, Jan; Kucerova, Ludmila; Burdova, Karolina (Manufacturing Technology Journal, 2020)
In this paper, the properties of three low carbon steels containing different percentage of manganese (1.5 or 3 wt%) and aluminium (1.5 or 2 wt %) were tested using dilatometric analysis and metallog-raphy. The steels had chemical compositions typical for TRIP (Transformation induced plasticity) steels and the two steels with an increased manganese content already belonged to the third genera-tion of AHS (advanced high strength) steels. The dilatometric measurement was employed not only to determine the characteristic transformation temperatures but also to simulate the heat treatment procedure commonly used for TRIP steels. Resulting microstructures obtained through this simula-tion were evaluated and compared. The two main alloying elements were proved to have a significant effect on the transition temperatures and thus on the processability and overall resulting properties of the material.
Keywords: Dilatometric Analysis; TRIP steel; Bainitic Steel; CCT Diagram; Transformation Temperature